A new species of Tarphius Erichson, 1845 (Coleoptera: Zopheridae) from Iran - Müller, Jörg; Schuh, Rudolf (Zootaxa, 2021)
The Hyrcanian Forest, located south of the Caspian Sea, represents a remarkably intact temperate forest ecosystem containing large numbers of endemic plants and animals, including beetles. Here we describe a new species of Tarphius Erichson, 1845 (Coleoptera: Zopheridae Solier, 1834) as the currently most eastern Tarphius species known. Tarphius hyrcanicus n. sp. is the first Tarphius species recorded from the Middle East. Its habitat and geographic positions are also reported. The discovery of this presumably endemic species in the Hyrcanian Forest underlines the importance of this Tertiary forest relict in the conservation of the biodiversity of temperate forests.